The Association of Maternal Emotional Status With Child Over-Use of Electronic Devices During the COVID-19 Pandemic - Guo, Xiangrong; Zhou, Yulai; Xu, Jian; Hu, Yuelai; Liu, Zhiwei (Frontiers in Pediatrics, 2021)
The quarantine during the COVID-19 pandemic may generate high levels of maternal depression/anxiety, and maternal emotional status may affect child behavioral development. Online education during the pandemic may induce child over-use of electronic-devices. However, child electronic-device over-use (especially among children under 12 who are immature in physical and mental development) during the pandemic has not attracted sufficient attention, and the association of child over-use with maternal emotional status remains unknown. Therefore, this study aims to assess the characteristics of child electronic-device over-use and the association between maternal emotional status and child over-use among 1,300 children from nurseries (<3 years), kindergartens (3-6 years) and primary schools (6-12 years) in Shanghai and Wuhan during COVID-19. Mothers completed an online questionnaire (including the Self-Rating-Depression/Anxiety-Scales and Family-Environment-Scale). The use of electronic devices (mobile-phones, iPads, computers, and televisions) and online courses taken by the children were investigated. Associations of maternal emotional status with electronic-device-use by child age were analyzed. The proportions of children in nurseries, kindergartens and primary schools were 8.5%, 44.5% and 47.0%, their percentages following online-courses were 24.5%, 48.4% and 99.0%, and their rates of electronic-device over-use were 34.2%, 62.2% and 93.4%, respectively. Significant associations were observed between higher maternal anxiety/depression levels and higher risks of mobile-phone/iPad over-use among preschoolers and primary-school students. Lower family intimacy and higher conflict levels were associated with higher maternal depression/anxiety levels and higher risks of electronic-device over-use. Our findings suggested that over-use of electronic-device among children under 12 was common during COVID-19, especially among children ≥6 years, and online-teaching may exacerbate over-use. Maternal anxiety/depression levels were associated with over-use of portable internet-devices (mobile-phone/iPad), especially among preschoolers and school-aged students, and family environment may mediate the association. These findings may contribute to better understanding of factors leading to over-use of electronic-device and developing strategies to decrease over-use during COVID-19.